The administration of valproic acid exerts a protective effect by reducing the infarct size and the triggering of ventricular fibrillation in an experimental model of chronic myocardial infarction. (3rd October 2022) - Genoves, P; Arias-Mutis, O J; Parra-Giraldo, G; Such-Miquel, L; Del Canto Serrano, I; Zarzoso, M; Ortiz-Guzman, J; Alberola Aguilar, A; Such-Belenguer, L; Chorro Gasco, F J
Abstract: Introduction: In myocardial infarction there are complications associated with adverse cardiac remodeling that occurs during the fibrotic process, producing an arrhythmogenic substrate that favors the triggering of ventricular arrhythmias such as ventricular fibrillation (VF). These complications also contribute to infarct expansion and mortality. Purpose: To analyze, in a model of chronic infarction (5 weeks) in rabbits, the effects of valproic acid (VA), an inhibitor of histone deacetylase enzymes, on the inducibility of ventricular fibrillation and infarct size. Methods: 47 New Zealand rabbits were assigned to sham (n=15), control (n=22) and VA-treated (n=10) groups. After midsternal thoracotomy and pericardiotomy, the circumflex coronary artery was occluded (1 hour), followed by reperfusion (control and treated groups). 500 mg/kg of VA were administered every 24 hours for 5 weeks. Then, the animals were sacrificed, their hearts excised and placed in a Langendorff perfusion system. We used a multielectrode recording plate (256 electrodes) and ventricular stimulation electrodes in the left ventricular epicardium. The inducibility of VF was analyzed using ventricular extrastimulus tests (VEST) with two basic stimulation cycle lengths (250 and 150 ms) and up to the three extrastimuli in each cycle. VEST was applied in four peri-infarct stimulation zones. After the electrophysiological study, the circumflex coronary artery was occluded, and the aorta was perfused with thioflavin-S to determine the area at risk (AR). We made sections of the left ventricle (LV) which were incubated in a triphenyltetrazolium chloride solution to determine the infarct size. The images obtained were digitized and manually quantified. The quantification was performed in 3 sections, located below the ligature of the coronary occlusion. Unpaired Student's t-test or chi-square test were used when appropriate (p<0.05). Results: Infarct size decreased in the VA-treated group compared to the control group, when expressed as a percentage of AR (40.3±5.3% vs. 69.8±20.4%, respectively) and when expressed as percentage of LV (19.3±7.8% vs. 38.6±16.4% respectively). The myocardium of the sham group did not exhibit areas of necrosis. Regarding VF inducibility, the treated group presented lower arrhythmia inducibility, regardless of the number of extrastimuli and pacing cycle length, triggering the arrhythmia in 40% of cases compared to 59% in the control group (p=0.011). Likewise, more extrastimuli were needed in VA-treated animals to trigger VF than controls (2 (50%) and 3 (50%) extrastimuli vs. 1 (15%), 2 (46%) and 3 (38%) extrastimuli needed, respectively; χ 2 =16.526; p<0.005). Conclusion: VA did exhibit a protective effect, as shown by its ability to limit the extension of the infarct size and to reduce the inducibility of ventricular fibrillation. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Carlos III Health Institute and Institute of Health Research (INCLIVA)